The Role of Scout Extracurricular in Effort To Student’s Social – Emotional Character Development (SECD) Competence - Syawal, Insani Nur (Universitas Pendidikan Indonesia, 2019)
This research is motivated by problems that have been found such as antipathy, lack of emotional control, undisciplined, ignorant of the environment, less communicative, and inability to make decisions. This study aims to look at the role of scouts extracurricular in the competence of students' social and emotional character development. The research method used in this research is a qualitative approach using a descriptive method, with a case study research design with the research subjects as supervisors, unit builders, board members and members of the scouts at 19 Junior High School, Bandung. Data collection techniques used by researchers are in-depth interviews, observation, and documentation studies. The results showed that the scout extracurricular contributed significantly to the development of social and emotional character including self-awareness, self-management (regulation), social awareness, relationship skills and responsible decision making. The author provides recommendations for schools to be more morally and materially supportive so that scouts extracurricular activities at SMP Negeri 19 Bandung can be more advanced and produce more students who are achievers and smart at the social and emotional competence, also become a good educational activity, not just mere formalities.